Nutritional composition, fatty acid profile, phytochemistry and evaluation of the effects of Carya illinoinensis on diabetes - Santos, Lorenna Lino; Lima De Almeida, Pedro Costa; Rodrigues, Carla Aparecida; Franco De Battisti, Luis Felipe; Costa, Lellis Henrique; Bastos, Renan Gomes; De Oliveira, Carla Miguel; Ferraz, Vany Perpetua; Leite Moraes, Ana Lucia; Almeida Paula, Hudsara Aparecida de; Araujo Paula, Fernanda Borges de; Dias Silva, Marcelo Jose [UNESP]; et al. (Wiley-Blackwell, 2019)
The increase in chronic diseases has arisen interest to search for alternative treatments so that people can improve their quality of life. Thus, Carya illinoinensis is the subject of the present work which aims at determining whether it has antidiabetic activity. The plant was collected and its nuts were separated from their peels, dried and grinded and incorporated into the feed, in concentration of 6% and 10%, for the treatment of animals. The centesimal composition of this diet was also determined. From the nut was also obtained the fixed oil, for the profile of fatty acids, and the 70% hydroethanolic extract for the phytochemical analysis. The results have shown that species presents hypoglycaemic effect, high fat composition of unsaturated fatty acids and the presence of some phenolic compounds, directly related to the antidiabetic activity. Therefore, the specie presente benefits that can contribute to the binomial diet/health.
Keywords: Carya illinoinensis; fatty acids; fixed oil; hypoglycaemic effect